Treating a Patient with Bone Marrow Edema Syndrome with Iloprost - mojtaba piri; mohammadsaleh sadeghi (Fasa University of Medical Sciences, 2015)
Bone Marrow Edema Syndrome (BMES) is an uncommon, self-limited and with unknown etiology characterized by severe pain with no history of trauma. Due to low prevalence of BMES and its non-specific signs, correct diagnosis is often delayed intensifying bone pain and impairing patients' function and quality of life. In this study we treated a patient with bone marrow edema syndrome in right ankle with Iloprost successfully that suffered pain in this region almost 4 months and NSAID, physiotherapy and steroid treatments was not benefited.